Latex Yield and Tree Growth in Kanchannagar Rubber Estate of Bangladesh - a Preliminary Study (Chittagong University Journal of Biological Sciences, 2024)
Rubber (Hevea brasiliensis Muell. Arg.) is a perennial, hardy and moderately quick-growing tree of the tropical regions (Khisa 1991). An initiative of its cultivation was taken in Bangladesh during 1960-61 considering the multiple uses of the latex and its products including the utility of timber (Chowdhury 1974). In Bangladesh, experts recommended its cultivation in the hilly land, terrace mostly evaluating the land suitability class and within the limitation of climatic factors (Hasan 1983). Bangladesh   Forest Industry Development Cooperation (BFIOC) sent a proposal to Bangladesh Forest Research Institute (BFRl), Chittagong to find out the causes of latex yield variation in the rubber station of Rangamatia and Doluchari of Kanchannagar Rubber Estate of Fatickchhari upazila of Chittagong District. Thus, a preliminary study was conducted on these rubber gardens during 2007-08. The clones in those estates are RRlM-600; PBIG/GG, GT-1 and PB-235, which were planted during different planting years (BFIDC 1993). Management of the Doluchari garden was comparatively better than Rangamatia. Total number of trees in Doluchari and Rangamatia is 29850 and .36149 respectively. Two (2004-06) years latex yield records showed that average productions were 3.16 kg/tre/yr for Doluchari and 1.86 kg/tree/yr in Rangamatia. The latex yield variation may be due to different factors viz: site quality, management efficiency, age group of clones, etc. (Anon,1989). The Chittagong Univ. J. B. Sci. 8(1&2): 33-36, 2013